1990
DOI: 10.1111/j.1475-2743.1990.tb00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between mycorrhizae and diseases caused by soil‐borne fungi

Abstract: . There are many records of mycorrhizae, particularly ectomycorrhizae, protecting roots against soil‐borne plant pathogens, though fungal or viral diseases of the green parts are usually more severe in mycorrhizal plants. There are various mechanisms by which mycorrhizae protect themselves against soil‐borne diseases. The occurrence and ecological significance of these mechanisms are discussed in relation to environmental factors. Mycorrhizae will probably become a very effective means of biological control on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…It is evident from these that (i), the biocontrol response is variable, with protection against fungal and nematode pathogens frequent but not universal, (ii), because experiments in the past have only usually tested single AMF and a single host genotype, * FAX No: +441224713423. E-mail: j.norman@ab.sac.ac.uk diversity within AMF for biocontrol of plant pathogens is unknown and (iii), very little is understood of the mechanisms involved in AMF invoked protection (Perrin, 1990). An understanding of the latter is particularly important if the consistency of response required for commercial application of AMF as agents of biocontrol is to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident from these that (i), the biocontrol response is variable, with protection against fungal and nematode pathogens frequent but not universal, (ii), because experiments in the past have only usually tested single AMF and a single host genotype, * FAX No: +441224713423. E-mail: j.norman@ab.sac.ac.uk diversity within AMF for biocontrol of plant pathogens is unknown and (iii), very little is understood of the mechanisms involved in AMF invoked protection (Perrin, 1990). An understanding of the latter is particularly important if the consistency of response required for commercial application of AMF as agents of biocontrol is to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Plant diseases caused by soilborne fungi are usually affected by the formation of mycorrhizas, and mycorrhizas are known to be effective in inhibiting the development of pathogens and reducing incidence of the disease (Dehne, 1982;Caron, 1989;Perrin, 1990). Although most plant species, including a large number of crops, can develop mycorrhizas, Cruciferae is an exceptional plant family, with few or no mycorrhizas (Ocampo et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 indicates that the maximum increase in root length was found in dual inoculation of A.laevis plus T.viride. Perrin(1990) found that mycorrhizal inoculation protects the roots from soil pathogens and tends to increase growth of roots. The maximum increase in root length might be due to mycelial network of AM fungi which extends deeper to invade nutrient depletion zone.…”
Section: Resultsmentioning
confidence: 99%